Early-age behaviour of the concrete surrounding a turbine spiral case : monitoring and thermo-mechanical modelling - Conceição, José (2014)
Within massive structures hydration reactions of the cement present in the mixture promote an internal heat release. Due to the low thermal conductivity of concrete, the dissipation rate of this thermal energy is lower than the rate of production of hydration heat, so considerable temperature gradients occur. Therefore, thermal stresses arise as a consequence of differential thermal expansions or contractions. These self-induced stresses may be even higher in the scenario of additional external restraints (such as support conditions). If not adequately controlled, the self-induced tensile stresses may induce cracking of concrete at early ages. This paper describes the in-depth analysis of the concrete surrounding the spiral case of a hydroelectric turbine constructed in Brazil, with a comprehensive approach that includes: laboratory characterization of the concrete properties, numerical analyses to predict the temperature and stress fields, and the corresponding in-field monitoring. The consistency obtained between numerical results and in situ observations is discussed in detail. The thermally induced cracking risk is also evaluated.